Recognition of the vocationalization process in tourism villages as potential sources of non-formal education in Indonesia: a TVET framework perspective - Bawono, Septiono Eko; Sudira, Putu; Nugraheni, Mutiara; Prihandini, Tinesa Fara; Sahria, Yoga (Jurnal Pendidikan Teknologi dan Kejuruan, 2024)
The challenges of socioeconomic loss due to the increasing number of unemployed persons, especially in rural areas, remain high. Tourist villages, comprising villagers' activities and local attractions in rural areas, are a potential source that can accommodate people to meet job needs. This study aims to define the roles, tasks, knowledge, skills, attributes, and functional areas of competence in tourist villages. The research was conducted in three tourist villages, namely Segajih, Jatimulyo, and Tinalah, in the Yogyakarta Special Region Province. The study employed a qualitative approach with research steps consisting of field observation, in-depth interviews, data generation, data analysis, and expert judgment. Data analysis refers to the Regional Model Competence Standard of Technical and Vocational Education and Training (TVET). The results showed that tourist villages play a role and task for the people as a life-based learning approach. The implementation of these roles and tasks requires knowledge, skills, and attributes, representing the functional areas of competence. Tourist villages have the opportunity to create jobs for the people; however, the community expresses concerns about skills improvement, such as social and emotional skills, cognitive and metacognitive skills, basic digital skills, as well as green job skills.